Rainfall thresholds for the precipitation of carbonate and evaporite minerals in modern lakes in northern China. Issue 14 (29th July 2015) - Gu, Ning; Jiang, Wenying; Wang, Luo; Zhang, Enlou; Yang, Shiling; Xiong, Shangfa
Abstract: Authigenic carbonate and evaporite minerals in lake sediments are widely used to qualitatively reconstruct climate. However, uncertainties still remain about their quantitative relationship to climate. Here we investigate 86 modern lakes in northern China to examine the relationships between mineral formation, lake water chemistry, and climate. The results show that from east to west, with increasing salinity and ionic concentration, calcite, dolomite, and evaporite minerals (gypsum and halite) occur in sequence. Their eastern boundaries approximate modern isohyets, and we define for the first time rainfall thresholds of 600 mm, 400 mm, and 350 mm for the formation of calcite, dolomite, and evaporite minerals, respectively. Since the 400 mm and 600 mm isohyets also coincide with vegetation boundaries, our findings enable a new approach for the quantitative reconstruction of paleoprecipitation and paleovegetation based on mineral analysis. Key Points: Lacustrine authigenic mineral formation in relation to climate is examined The thresholds for the formation of different minerals are 600, 400, and 350 mm Carbonates and evaporites can help in quantitative paleoclimate reconstruction